Secondary Attachment Disc of Edible Seaweed Chondracanthus Chamissoi (Rhodophyta, Gigartinales): Establishment of Permanent Thalli Stock - Remonsellez-Rojas, J (Elsevier B.V., 2021)
In this study we evaluated the productivity of an outdoor cultivation system based in secondary attachment discs (SADs) of Chondracanthus chamissoi as propagation strategy to produce and maintain a permanent thalli stock. For that, re-attachment of fronds, survival of SADs, growth rate of new erect axes, coverage and productivity were evaluated in three different artificial substrates: fiberglass plates, ceramic plates and PVC pipes. C. chamissoi SADs were formed in all three substrates, and they developed new erect axes reaching >6 mm length after 12 weeks. Ceramic and fiberglass plates were the substrates with the best performance. Nonetheless, the cultivation system using fiberglass was the most suitable one, since it presented a higher survival of the SADs and a better use of tank space, improving the amount of seaweeds growing inside the tanks. Based on the results, the estimated cultivation using fiberglass plates would allow to produce 31,993 SADs on a 3m3 tank after 90 days. This technology would allow: (i) to produce thalli to be used as propagules for seaweed cultivation based on vegetative propagation, since nowadays this depends of thalli from natural populations; (ii) to propagate and maintain a thalli stock with desirable commercial traits, providing an better biomass quality, (iii) to grow and maintain thalli in the same tank from diverse localities and/or reproductive phase; optimizing resources and space, which currently is not feasible using free-floating systems, due to the difficulty to recognize isomorphic haploid and diploid phases, and (iv) to adopt this strategy in other red seaweeds of commercial interest, such as the genus Chondracanthus, Gigartina and Solieria. © 2020 Elsevier B.V.